Corneal ectasia risk and percentage tissue altered in myopic patients presenting for refractive surgery - Ong, Hon Shing (2020)
Purpose: A percentage tissue altered (PTA) score of ≥40% has been advocated as an independent indicator of post-operative ectasia risk following laser in-situ keratomileusis (LASIK). This study was performed to test the hypothesis that refractive procedures, such as laser-assisted subepithelial keratectomy (LASEK) or small incision lenticule extraction (SMILE), may alter the range of PTA, within which refractive corneal surgery can be safely performed. Setting: Refractive department, tertiary ophthalmic hospital. Design: Retrospective observational study. Methods: Review of case notes was performed for patients who presented for refractive surgeries, other than LASIK. To determine the risk of corneal ectasia for each patient prior to refractive surgery, we estimated what each patient’s PTA would have been if they had undergone LASIK. The Randleman Ectasia Risk Score System (ERSS) was also calculated. Results: 114 eyes (66 patients) were included. 94 eyes underwent SMILE. 20 eyes underwent LASEK. A significant proportion of eyes had PTA ≥40% – SMILE eyes: up to 31.9%, LASEK eyes: up to 60.0% (at presumed LASIK flap of 120 μm). The maximum calculated PTAwas up to 47.9% in the SMILE group and up to 51.5% in the LASEK group. Using ERSS, 12.8–16% of SMILE eyes and 15.0–80.0% of LASEK eyes would have been considered to have moderate-tohigh ectasia risk. No post-surgical ectasia was observed at 3 years. Conclusion: SMILE and LASEK alter the range of PTA, within which corneal refractive surgery may be performed with a lower risk of developing post-operative corneal ectasia; a safe PTA threshold needs to be determined for these procedures before recommendations for clinical practice can be made.